Penyalahgunaan Dokumen Jamaah Umrah Terhadap Akses Masuk Raudhah - Lubis, Ibra Hatigoran; Razaq, Abdul (Jayapangus Press, 2026)
Umrah is a widely practiced Sunnah worship that continues to attract a growing number of pilgrims, including those from Indonesia, alongside the ongoing digital transformation of Hajj and Umrah services. While digitalization aims to enhance efficiency and access control, limited empirical studies have examined document misuse within regulated worship spaces, particularly access to the Raudhah. This study addresses this gap by investigating the forms of Umrah pilgrim document misuse, identifying contributing factors, and analyzing its implications for access governance and service quality at the Raudhah. Using a qualitative approach, data were collected through interviews, field observations, and analysis of official documents. The findings reveal that document misuse occurs through identity manipulation, unauthorized use of group schedules, and falsification of reservation evidence. These practices are driven by high demand for Raudhah access, quota limitations, weak supervision, and low digital literacy among pilgrims and organizers. The study contributes empirically to the discourse on Umrah governance by highlighting vulnerabilities in digital access systems and offering policy-oriented recommendations to strengthen verification mechanisms and inter-institutional coordination.